Computerized registry as a potential tool for surveillance and management of complex bone and joint infections in France: French registry of complex bone and joint infections. Issue 10 (1st October 2020) - Lemaignen, Adrien; Grammatico-Guillon, Leslie; Astagneau, Pascal; Marmor, Simon; Ferry, Tristan; Jolivet-Gougeon, Anne; Senneville, Eric; Bernard, Louis
Abstract : Aims: The French registry for complex bone and joint infections (C-BJIs) was created in 2012 in order to facilitate a homogeneous management of patients presented for multidisciplinary advice in referral centres for C-BJI, to monitor their activity and to produce epidemiological data. We aimed here to present the genesis and characteristics of this national registry and provide the analysis of its data quality. Methods: A centralized online secured database gathering the electronic case report forms (eCRFs) was filled for every patient presented in multidisciplinary meetings (MM) among the 24 French referral centres. Metrics of this registry were described between 2012 and 2016. Data quality was assessed by comparing essential items from the registry with a controlled dataset extracted from medical charts of a random sample of patients from each centre. Internal completeness and consistency were calculated. Results: Between 2012 and 2016, 30, 607 presentations in MM were recorded corresponding to 17, 748 individual patients (mean age 62.1 years (SD 18.4); 10, 961 (61.8%) males). BJI was considered as complex for 63% of cases (n = 19, 355), and 13, 376 (44%) had prosthetic joint infections (PJIs). The controlled dataset, available for 19 centres, included 283 patients. Global consistency and completeness were estimated at 88.2% and 88.9%, respectively, considering missing items in the eCRFs as negative results. Conclusion: This national registry is one of the largest prospective databases on BJI and its acceptable data quality parameters allow further use for epidemiological purposes. Cite this article: Bone Joint Res 2020;9(10):635–644.